SISTEM MONITORING PEMBAYARAN DAN BIMBINGAN KONSELING (BK) SEKOLAH MENENGAH ATAS BRBASIS AUTO RESPON SMS GATEWAY (TUDI KASUS SMA NASIMA) (Information Technology and Telematics, 2013)
The development in technology and information is not only used as a means of ease in getting information or communication, but also has become an inherent part of the daily life of the community, especially in schools. It can be applied to the payment system of monitoring and guidance counseling in high schools by using SMS Gateway-based auto response. In general, schools are still using System monitoring payments and counseling by hand so that the system is more ineffective and inefficient, so in making this thesis will design and build a system of monitoring and counseling payments automatically through the auto-response media-based SMS gateway so that can be effective and efficient in the school. This monitoring system uses an auto response SMS gateway and also using RFID as a means of identification in terms of data input Automator students who make payments and counseling records making it easier to incorporate student data. With the design of payment and monitoring system based counseling sms gateway auto response is expected to make the school system more effective, efficient and more accurate. Keywords - Monitoring system, auto-response SMS Gateway, RFID Identification